(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
In this work the investigation determine the discrete analogues of analytical dependences with the use of geometrical set of superposition has been continued to be carried out. Power series functions, exponential, logarithmic functions has been investigated. The results can be used for the discrete design of geometrical characters in engineering and construction with the use numerical sequencesof the above-stated analytical dependences and without generating and working out of linear equation systems. Keywords: discrete geometrical design, method offinite differences, recurrent dependences, mathematical set of numerical sequences, geometrical set of superposition